Virulence factors of Aggregatibacter actinomycetemcomitans - A status update - Rajvir Malik; Radha Changela; Prerna Krishan; Shalini Gugnani; Deepika Bali (Journal of International Clinical Dental Research Organization, 2015)
Periodontitis is a chronic infectious inflammatory disease characterized by the destruction of tooth. The contribution of bacteria to the disease progression is poorly understood probably due to the multifactorial background of this disease. Aggregatibacter actinomycetemcomitans is part of the normal flora in many healthy individuals, but is also a major etiologic agent in some aggressive forms of periodontitis. The genetic diversity among different isolates of Aggregatibacter actinomycetemcomitans is great and its ability to express and release virulence factors varies. Aggregatibacter actinomycetemcomitans, a pathogen not only in periodontal but also in some nonoral infections, possesses several virulence determinants which contribute to its ability to colonize the oral cavity, persist in the periodontal pocket, resist and evade host defenses, cause destruction of soft and hard tooth-supporting tissues, and interfere with host tissue repair after infection. Authors conducted a comprehensive search through PubMed/Medline databases to compile the available literature till June 2014, for the purpose of detailed insight into the bacteria. The search was designed to identify appropriate articles related to virulence factors of Aggregatibacter actinomycetemcomitans, and the articles were independently screened for eligibility.